Formation mechanism of apex-truncated octahedral Cu2O microcrystal. Issue 42 (11th October 2016) - Yang, Sanjun; Liu, Qiming
Abstract : SO4 2− plays a pivotal role in the formation of the apex-truncated octahedral morphology of Cu2 O. Abstract : Corner-truncated octahedral Cu2 O microcrystal was synthesized by a typical solution phase reduction method with CuSO4, glucose, and a small amount of NaOH. Researching into the reaction process, we found that the Cu2 O microcrystal grew following the sol–gel growth model, instead of Lamer nucleation–diffusion model. The roles that OH − and SO4 2− played in the formation of the octahedral morphology were revealed by separating them and investigating the corresponding products, respectively. We used PVP (polyvinylpyrrolidone) in another experiment to show that the influence of the organic surfactant on the crystal habit may also be demonstrated more clearly using this method.